Integração entre ecologia de bacias hidrográficas e educação ambiental para a conservação dos rios da serra do mar no estado do Paraná - Marques, Paulo Henrique Carneiro (2004)
The catchment areas on the eastern and western slopes of Serra do Mar Mountains (Paraná state, Brasil) are sites of strategic interest to the conservation of riverine ecossystems, as they provide water supply to about 2,5 million people. The main objective of this study was to develop a riverine ecological research directly linked to an Environment Education program in public schools, in order to support a wide environmental planning for these spring areas. The study was developed troughout four guidelines, presented on the four chapters described below: Chapter I - Comparative ecological study of streams in western and eastern slopes of Serra do Mar Mountains, Paraná State, Brasil. This study was carried out in the Piraquara River Basin (eastern slope Upper Iguaçu River Basin) and the Marumbi River Basin (western slope Oceanic basin). The main objectives were to describe the limnological features of aquatic ecossystems and to analyse possible effects of the Serra do Mar Mountain slope as orographic barrier for the oceanic air masses loaded of humidity and nutrients. The results can be taken as an important basis for a wide biological monitoring program to the regional watersheds. Chapter II Watershed spatial zoning based on limnological variables: a methodology for environmental planning and Environmental Education. Starting from results presented in chapter one, this study presents a methodology of spatial zoning based on the aquatic environment features, standing out the advantages of this method for the watershed planning and monitoring. Furthermore, the benefits to support Environmental Education programs based on environmental study at different levels of educational curriculum were analised, as well as the methodology value as a didactical framework to improve the student comprehension about structure and function of lotic ecossystems and the relationship between water quality and anthropogenic effects. Chapter III - River basin assessment and their integration to the curriculum of primary and secondary formal education. Starting from the concept of River Basin as a natural unit for environmental management under ecological, social and economical points of wiew, this work was carried out with the goals of developing, applying and evaluating an Environment Education framework to river basins, troughout the study of local environmental problems. The framework embraced some methodological issues to environmental description and the development of a water quality analysis toolkit, based on the traditional tools of scientific procedures. The framework and the toolkit were tested and evaluated through an intervention program in public schools. Chapter IV Environmental Education and transversality: an experience on curriculum planning whith teachers of public schools in Curitiba Brasil. This paper describes a concrete experience of integrating Environmental Education on formal curriculum, based on the concept of transversality, in teachers formation classes applied to 350 teachers of 21 public schools (about 13% of the local public schools). Troughout a participatory framework, the teachers developed the integrated matrix of curriculum , founded on the technics of conceptual keywords mapping, in order to achieve a curricular planning centralized by the local environmental issues and problems of the watershed management.